Correlation of FT-IR fingerprint and α-glucosidase inhibitory activity of Salak (Salacca zalacca) fruit extracts utilizing orthogonal partial least square - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Mat So'ad, Siti Zaiton; Roheem, Fatimah; Bes-Bes, Salima Saidi; Khatib, Alfi (MDPI, 2018)
Salak fruit (Salacca zalacca), commonly known as snake fruit, is used indigenously as food and for medicinal applications in Southeast Asia. This study was conducted to evaluate the α-glucosidase inhibitory activity of salak fruit extracts in correlation to its Fourier transform infrared spectroscopy (FT-IR) fingerprint, utilizing orthogonal partial least square. This calibration model was applied to develop a rapid analytical method tool for quality control of this fruit. A total of 36 extracts prepared with different solvent ratios of ethanol–water (100, 80, 60, 40.20, 0% v/v) and their α-glucosidase inhibitory activities determined. The FT-IR spectra of ethanol–water extracts measured in the region of 400 and 4000 cm−1 at a resolution of 4 cm−1. Multivariate analysis with a combination of orthogonal partial least-squares (OPLS) algorithm was used to correlate the bioactivity of the samples with the FT-IR spectral data. The OPLS biplot model identified several functional groups (C–H, C=O, C–N, N–H, C–O, and C=C) which actively induced α-glucosidase inhibitory activity.